A coverage path planning approach for autonomous radiation mapping with a mobile robot - Abd Rahman N.A.; Sahari K.S.M.; Hamid N.A.; Hou Y.C. (SAGE Publications Inc., 2023)
Air navigation; Image segmentation; K-means clustering; Machine design; Mapping; Mobile robots; Motion planning; Radiotherapy; Robot programming; Coverage path planning; Field robotics; Hotspots; Mobile Robot Navigation; Radiation mapping; Radiation maps; Radiation safety; Radiation workers; Regions of interest; Sampling points; Radiation